Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2010
DOI: 10.1007/s10059-010-0117-9
|View full text |Cite
|
Sign up to set email alerts
|

Quercetin Enhances Human α7 Nicotinic Acetylcholine Receptor-Mediated Ion Current through Interactions with Ca2+ Binding Sites

Abstract: The flavonoid quercetin is a low molecular weight substance found in fruits and vegetables. Aside from its anti-oxidative effect, quercetin, like other flavonoids, has a wide range of neuropharmacological actions. The α7 nicotinic acetylcholine receptor (α7 nAChR) has a Ca(2+)-binding site, is highly permeable to the Ca(2+) ion, and plays important roles in Ca(2+)-related normal brain functions. Dysfunctions of α7 nAChR are associated with a variety of neurological disorders. In the present study, we investiga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
30
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(36 citation statements)
references
References 42 publications
5
30
1
Order By: Relevance
“…However, the underlying cellular mechanisms of quercetin actions are relatively unknown, especially with regards to possible regulation of receptors or ionic channels involved in synaptic transmissions. Recently, we demonstrated that quercetin differentially regulates subsets of nicotinic acetylcholine receptor such as homomeric glycine, 5-HT3A, α7 and α9α10 nicotinic acetylcholine receptors [17][18][19][20]. In the present study, we examined the effects of quercetin on heteromeric α3β4 nicotine acetylcholine receptor channel activity and report here that quercetin inhibits heteromeric α3β4 nicotine acetylcholine receptor channel activity with voltage-independent and non-competitive manner.…”
Section: Introductionmentioning
confidence: 79%
See 2 more Smart Citations
“…However, the underlying cellular mechanisms of quercetin actions are relatively unknown, especially with regards to possible regulation of receptors or ionic channels involved in synaptic transmissions. Recently, we demonstrated that quercetin differentially regulates subsets of nicotinic acetylcholine receptor such as homomeric glycine, 5-HT3A, α7 and α9α10 nicotinic acetylcholine receptors [17][18][19][20]. In the present study, we examined the effects of quercetin on heteromeric α3β4 nicotine acetylcholine receptor channel activity and report here that quercetin inhibits heteromeric α3β4 nicotine acetylcholine receptor channel activity with voltage-independent and non-competitive manner.…”
Section: Introductionmentioning
confidence: 79%
“…Electrophysiological experiments were performed three to five days after oocyte isolation. For α3β4 nicotine acetylcholine receptor experiments, α3 and β4 nicotine acetylcholine receptor subunit-encoding cRNAs (40 nl) were co-injected into the animal or vegetal pole of each oocyte 1 day after isolation using a 10-μl microdispenser (VWR Scientific, West Chester, PA, USA) fitted with a tapered glass pipette tip (15∼20 μm in diameter) [19].…”
Section: Preparation Of Xenopus Laevis Oocytes and Microinjectionmentioning
confidence: 99%
See 1 more Smart Citation
“…In previous studies, we demonstrated that quercetin regulates α3β4, α7 or α9α10 nicotinic acetylcholine receptor-gated ion currents [22][23][24]. For example, quercetin inhibited heteromeric α3β4 and α9α10 nicotinic acetylcholine receptor channel activities, whereas quercetin enhanced homomeric α7 nicotinic acetylcholine receptors, indicating a differential effect of quercetin on nicotinic acetylcholine receptor regulations.…”
Section: Non-competitive Inhibition Of α1β1δε Nicotinic Acetylcholinementioning
confidence: 81%
“…In previous reports, we have shown that quercetin regulates the Cys-loop family of ligand-gated ion channels, such as 5-HT3A, human glycine α1, α7, α9α10 and α3β4 nicotine acetylcholine receptors [20][21][22][23][24]. However, relatively little is known about the effects of quercetin on the muscle-type nicotinic acetylcholine receptor channel activity.…”
Section: Introductionmentioning
confidence: 99%